The relationship between entrepreneurship components and communication skills of managers: a structural equation modeling - Hossein Abadi , Saeeid; Pourrashidi, Rostam; Mollaei , Hamid Reza; Mohammad Bagheri , Mahdi (Social Determinants of Health, 2023)
Background: The purpose of this study was to look into how managerial integrity and the elements of academic entrepreneurship relate to one another. Methods: This research was descriptive-correlational in nature. 1832 people made up the statistical population of the survey, including management, staff, and faculty from Islamic Azad Universities in District 6. 315 individuals that were chosen using stratified random sampling made up the estimated sample size. Data collection method was an academic entrepreneurship questionnaire that included 23 questions and a managers’ good character questionnaire that included 26 questions. By using exploratory factor analysis, the dimensions of academic entrepreneurship were discovered, and the internal validity of the questionnaires was confirmed by Cronbach’s alpha (higher than 0.7). Results: The elements of academic entrepreneurship (organizational competencies, continuous contact, university aims and policies, entrepreneurial marketing, and culture) and the positive and substantial path coefficient (p = 0.001) were found to be significantly correlated. Conclusion: The change in educational quality and the investigation of the effective parameters for encouraging entrepreneurship in academic settings were the key factors in increasing the willingness for entrepreneurship. If the willingness for entrepreneurship was associated with a good character, it can have positive results and effectiveness that can be used by managers.